Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the value of [tex]\( a^3 + \frac{1}{a^3} \)[/tex] given that [tex]\( a^2 + \frac{1}{a^2} = 18 \)[/tex] and using only the positive value of [tex]\( a - \frac{1}{a} \)[/tex], we can follow these steps:
1. Find [tex]\( a \)[/tex] from [tex]\( a^2 + \frac{1}{a^2} = 18 \)[/tex]:
- We start with the equation [tex]\( a^2 + \frac{1}{a^2} = 18 \)[/tex].
- Denote [tex]\( x = a^2 \)[/tex]. Thus, the equation becomes [tex]\( x + \frac{1}{x} = 18 \)[/tex].
2. Solve for [tex]\( x \)[/tex]:
- Multiply both sides by [tex]\( x \)[/tex] to clear the fraction:
[tex]\[ x^2 + 1 = 18x \implies x^2 - 18x + 1 = 0 \][/tex]
- Solve the quadratic equation using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -18 \)[/tex], and [tex]\( c = 1 \)[/tex]:
[tex]\[ x = \frac{18 \pm \sqrt{18^2 - 4 \cdot 1 \cdot 1}}{2 \cdot 1} = \frac{18 \pm \sqrt{324 - 4}}{2} = \frac{18 \pm \sqrt{320}}{2} = \frac{18 \pm 4\sqrt{20}}{2} = 9 \pm 2\sqrt{5} \][/tex]
- Since [tex]\( x = a^2 \geq 0 \)[/tex], and [tex]\( 9 - 2\sqrt{5} \)[/tex] is a positive number, we have [tex]\( x = 9 + 2\sqrt{5} \)[/tex].
3. Find the positive value of [tex]\( a - \frac{1}{a} \)[/tex]:
- We know that [tex]\( a = \sqrt{x} \)[/tex], so [tex]\( a = \sqrt{9 + 2\sqrt{5}} \)[/tex].
- To work with [tex]\( \sqrt{x} \)[/tex], we rationalize [tex]\( \sqrt{x} = 2 + \sqrt{5} \)[/tex]. Thus, [tex]\( a = 2 + \sqrt{5} \)[/tex].
- Then calculate [tex]\( \frac{1}{a} \)[/tex]:
[tex]\[ \frac{1}{a} = \frac{1}{2 + \sqrt{5}} = 2 - \sqrt{5} \][/tex]
- Therefore,
[tex]\[ a - \frac{1}{a} = (2 + \sqrt{5}) - (2 - \sqrt{5}) = 2\sqrt{5} \][/tex]
4. Calculate [tex]\( a^3 + \frac{1}{a^3} \)[/tex]:
- We use the identity:
[tex]\[ \left(a + \frac{1}{a}\right)^3 = a^3 + \frac{1}{a^3} + 3\left(a + \frac{1}{a}\right) \][/tex]
- Given that:
[tex]\[ a^2 + \frac{1}{a^2} = 18 \quad \text{implies} \quad \left(a + \frac{1}{a}\right)^2 = a^2 + \frac{1}{a^2} + 2 = 18 + 2 = 20 \][/tex]
- Thus, [tex]\( a + \frac{1}{a} = \sqrt{20} = 2\sqrt{5} \)[/tex]:
[tex]\[ \left(2 + \sqrt{5} + 2 - \sqrt{5}\right)^3 = \left(2\sqrt{5}\right)^3 = 34\sqrt{5} \][/tex]
- Hence,
[tex]\[ a^3 + \frac{1}{a^3} = 34\sqrt{5} \][/tex]
Thus, the value of [tex]\( a^3 + \frac{1}{a^3} \)[/tex] is [tex]\( 34\sqrt{5} \)[/tex].
1. Find [tex]\( a \)[/tex] from [tex]\( a^2 + \frac{1}{a^2} = 18 \)[/tex]:
- We start with the equation [tex]\( a^2 + \frac{1}{a^2} = 18 \)[/tex].
- Denote [tex]\( x = a^2 \)[/tex]. Thus, the equation becomes [tex]\( x + \frac{1}{x} = 18 \)[/tex].
2. Solve for [tex]\( x \)[/tex]:
- Multiply both sides by [tex]\( x \)[/tex] to clear the fraction:
[tex]\[ x^2 + 1 = 18x \implies x^2 - 18x + 1 = 0 \][/tex]
- Solve the quadratic equation using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -18 \)[/tex], and [tex]\( c = 1 \)[/tex]:
[tex]\[ x = \frac{18 \pm \sqrt{18^2 - 4 \cdot 1 \cdot 1}}{2 \cdot 1} = \frac{18 \pm \sqrt{324 - 4}}{2} = \frac{18 \pm \sqrt{320}}{2} = \frac{18 \pm 4\sqrt{20}}{2} = 9 \pm 2\sqrt{5} \][/tex]
- Since [tex]\( x = a^2 \geq 0 \)[/tex], and [tex]\( 9 - 2\sqrt{5} \)[/tex] is a positive number, we have [tex]\( x = 9 + 2\sqrt{5} \)[/tex].
3. Find the positive value of [tex]\( a - \frac{1}{a} \)[/tex]:
- We know that [tex]\( a = \sqrt{x} \)[/tex], so [tex]\( a = \sqrt{9 + 2\sqrt{5}} \)[/tex].
- To work with [tex]\( \sqrt{x} \)[/tex], we rationalize [tex]\( \sqrt{x} = 2 + \sqrt{5} \)[/tex]. Thus, [tex]\( a = 2 + \sqrt{5} \)[/tex].
- Then calculate [tex]\( \frac{1}{a} \)[/tex]:
[tex]\[ \frac{1}{a} = \frac{1}{2 + \sqrt{5}} = 2 - \sqrt{5} \][/tex]
- Therefore,
[tex]\[ a - \frac{1}{a} = (2 + \sqrt{5}) - (2 - \sqrt{5}) = 2\sqrt{5} \][/tex]
4. Calculate [tex]\( a^3 + \frac{1}{a^3} \)[/tex]:
- We use the identity:
[tex]\[ \left(a + \frac{1}{a}\right)^3 = a^3 + \frac{1}{a^3} + 3\left(a + \frac{1}{a}\right) \][/tex]
- Given that:
[tex]\[ a^2 + \frac{1}{a^2} = 18 \quad \text{implies} \quad \left(a + \frac{1}{a}\right)^2 = a^2 + \frac{1}{a^2} + 2 = 18 + 2 = 20 \][/tex]
- Thus, [tex]\( a + \frac{1}{a} = \sqrt{20} = 2\sqrt{5} \)[/tex]:
[tex]\[ \left(2 + \sqrt{5} + 2 - \sqrt{5}\right)^3 = \left(2\sqrt{5}\right)^3 = 34\sqrt{5} \][/tex]
- Hence,
[tex]\[ a^3 + \frac{1}{a^3} = 34\sqrt{5} \][/tex]
Thus, the value of [tex]\( a^3 + \frac{1}{a^3} \)[/tex] is [tex]\( 34\sqrt{5} \)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.